2012
DOI: 10.1530/eje-12-0422
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol acutely inhibits whole body lipid oxidation and attenuates lipolysis in subcutaneous adipose tissue: a randomized, placebo-controlled study in postmenopausal women

Abstract: Context: Estradiol (E 2 ) promotes and maintains the female phenotype characterized by subcutaneous fat accumulation. There is evidence to suggest that this effect is due to increased anti-lipolytic a2A-adrenergic receptors, but whether this requires long-term exposure to E 2 or is an immediate effect is not clear. Objective: To study acute effects of a single dose (4 mg) of 17b-E 2 on regional and systemic lipolysis. Methods: Sixteen postmenopausal women (age, 59G5 years; weight, 67G10 kg; and BMI, 24.8G2.9) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
0
26
0
3
Order By: Relevance
“…Obviously more collagen than men accumulated by premenopausal women implied that a young lady has a high level collagen formation capacity while the postmenopausal hasn't. These come outs manifest that the female hormones are related to collagen deposition, and the estrogen is a protected factor of AL presumably and mediately (Markiewicz et al, 2007;Aznal et al, 2012;Gormsen et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Obviously more collagen than men accumulated by premenopausal women implied that a young lady has a high level collagen formation capacity while the postmenopausal hasn't. These come outs manifest that the female hormones are related to collagen deposition, and the estrogen is a protected factor of AL presumably and mediately (Markiewicz et al, 2007;Aznal et al, 2012;Gormsen et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…13,28 In humans, a single dose of E2 attenuated catecholamine-stimulated lipolysis in femoral subcutaneous adipose. 7 In our hands, CL was equally effective in increasing whole-body lipolysis in SHAM, OVX and OVX E2 rats. Unlike Darimont et al, 15 who found increased responsiveness of subcutaneous adipose to isoproterenol infusion after 7 d of E2 injection, we did not observe an augmentation of serum FFA or glycerol in OVX E2 rats after 2 weeks of treatment.…”
Section: Discussionmentioning
confidence: 51%
“…The changes we 32 and others. 7,14 have observed in subcutaneous tissue suggest it may be more affected by the chronic absence of E2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Под влиянием эстрадиола увеличивается экспрес-сия антилиполитических α2A-адренергических рецеп-торов в подкожной жировой клетчатке, в особенности в феморальной области, в то время как в ВЖТ данный эффект отсутствует [34]. Назначение эстрадиола кры-сам с удаленными яичниками приводило к увеличе-нию утилизации глюкозы адипоцитами, снижению артериального давления, концентрации инсулина, увеличению экспрессии рецепторов, активирующих пролиферацию пероксисом-гамма (PPAR-γ) в адипо-цитах, в то время как экспрессия PPAR-α возрастала в печени [35].…”
Section: ожирение и метаболизмunclassified